The structure of basin-scale internal waves in a stratified lake in response to lake bathymetry and wind spatial and temporal distribution: Lake Iseo, Italy - Valerio, G.; Pilotti, M.; Marti, Clelia; Imberger, J. (American Society of Limnology and Oceanography, Inc., 2012)
Field data, theoretical analyses, and numerical simulations were used to investigate the effects of lake basin bathymetry and spatial and temporal structures of the wind field on the basin-scale internal wave spectrum in Lake Iseo. This deep Italian basin is characterized by the presence of a large island, imparting attributes of an annulus to the lake. During the summer of 2010, the internal wave activity was dominated by a basin-scale internal wave of vertical and horizontal modes 1 (V1H1), superimposed on which were occasional higher vertical modes (V2H1) and higher horizontal modes (V1H5) trapped by the main island. The occurrence of these motions was interpreted as forcing by the wind components with similar horizontal structures and with energies at frequencies near the natural oscillations of the excited modes. The modifications of the wind field by the topography, in particular, controlled the excitation of an anticyclonic wave trapped around the island, whose features were investigated on the basis of an extension of the circular model to the case of an annular basin of constant depth. © 2012, by the Association for the Sciences of Limnology and Oceanography, Inc.